Re-reading B. S. Johnson
XVIII, 246 p. 1 illus.
Keywords: Growing academic interest and the republication of B.S. Johnson's major works have been reinforced by Coe's award-winning biography Like A Fiery Elephant (2004). With a preface by Coe, this collection, co-edited by two leading Johnson scholars, offers an annotated bibliography, a chronology and readings of the author and his work.